Planejamento, síntese e avaliação da atividade antinociceptiva e toxicidade aguda de arilfuranos como potenciais inibidores da enzima FAAH. - Pedro Augusto Lemos Santana (2024)
The endocannabinoid system plays a crucial role in various pathophysiological functions and is being intensely studied for the development of drugs for managing inflammatory, painful, and neurodegenerative conditions. This system consists of receptors, enzymes, and endogenous ligands, with anandamide (AEA) being a standout among the latter, showing significant activity in various pain models. However, its short half-life is due to rapid metabolism by the fatty acid amide hydrolase (FAAH) enzyme. OL-135 is a keto-oxazolopyridine derivative with notable inhibitory activity (IC50 = 4.7 nM) against FAAH. In this context, 44 arylfuran analogs of OL-135 were proposed in the present study, with two of them (analogs 2 and 11) synthesized, characterized, and tested in acute pain models. Substance 2 reduced mechanical allodynia at doses of up to 1 mg/kg, carrageenan-induced paw edema, and increased nociception latency at doses exceeding 5 mg/kg, without causing alterations in the characteristic biochemical parameters of cardio, hepatic, or nephrotoxicity. The binding modes of substance 2 and other arylfuran analogs at the enzyme binding site were proposed through molecular docking using three distinct protocols, revealing potential interactions similar to those of known FAAH inhibitors. These analogs demonstrate significant potential to aid in the design of analgesic and anti-inflammatory substances by inhibiting components of the endocannabinoid system.